Technological Anxiety of Older Adults in Seeking Medical Attention: Concept, Current Status, and Influencing Factors - Hou Yongmei (Science and Technology: Developments and Applications Vol. 4, 2025)
Background: The combination of the Internet and health management services has improved the efficiency of medical work, but it has also brought increasing anxiety about medical technology to people, especially to the elderly with low educational level and cognitive ability. Objective: The objective of the study is to understand the current situation, causes, and main influencing factors of medical technology anxiety among the elderly. Methods: The literature retrieval method was used to review empirical papers published in English or Chinese in the past 20 years in PubMed, Google Scholar, CNKI, and the Wanfang database. Results: Thirty-five articles were included. The medical technology anxiety of the elderly is significantly higher than those of other age groups, and the direct cause is the low digital skills of the elderly. This situation is influenced by multiple factors in multiple systems, including individuals, families, communities, and society, and the factors of each system are intertwined and work together. Conclusion: Technological anxiety in seeking medical attention hinders the elderly from obtaining healthcare services through digital health technology. However, related research is still in its infancy, and there is an urgent need for in-depth research on the influencing factors, mechanisms, intervention pathways, and implementation techniques of technological anxiety in elderly medical care.